Batu Teong di Pegunungan Kota Ambon, Kepulauan Ambon Lease - Lucas Wattimena (Kapata Arkeologi, 2016)
This paper discusses the traces of prehistoric communities in the mountainous region of the Ambon island. This study is more directed to archaeological findings in the form of material culture that is dolmen in expressing their cosmology. Cosmology discussion in this paper is about understanding and views of people in the mountain region of the city of Ambon, Ambon Island on settlement patterns and understanding symbols dolmen. The purpose of writing is to know the and understand the views and understanding of the people in the mountainous region of Ambon City in  Ambon Island on settlement patterns and understanding symbols based on material culture dolmen. Methods ethnoarchaeology the basis for the reviewers' problems referred to with reference to the interview data collection techniques, survey and literature study. The results showed that 1) people in the mountainous region of the city of Ambon, Ambon Island know as stone dolmen Teong, the stone which symbolizes about grouping integrated community. 2) The settlement pattern of people in the mountainous region of the city of Ambon, Ambon Island based cultural material of stone dolmen Teong characterized micro settlements, ie settlements which focuses on the center of the stone dolmen Teong as central settlement. Macro-economic settlement of people in the mountainous region of the city of Ambon, Ambon Island has a characteristic orientation (cosmos) coastal settlement - the mountain. The orientation can be seen in the forms of settlement which extends linearly follow the directions north south and cosmos them about splitting the island, or in other words do not follow geographical settlements length of the island.Tulisan ini membahas tentang bagaimana jejak-jejak prasejarah orang-orang pegunungan di wilayah Pulau Ambon. Kajian ini lebih mengarah kepada temuan arkeologi berupa budaya material yaitu dolmen dalam mengungkapkan kosmologi mereka. Pembahasan kosmologi dalam tulisan ini adalah mengenai pemahaman dan pandangan orang-orang di wilayah pegunungan Kota Ambon, Pulau Ambon tentang pola permukiman dan pemaknaan simbol dolmen. Tujuan penulisan adalah untuk mengatahui dan memahami pandangan dan pemahaman orang-orang di wilayah pegunungan Kota Ambon, Pulau Ambon tentang pola permukiman dan pemaknaan simbol berdasarkan budaya bendawi dolmen. Metode etnoarkeologi menjadi dasar dalam penelaah permasalahan dimaksud dengan mengacu pada teknik pengumpulan data wawancara, survei dan studi kepustakaan. Hasil penelitian menunjukan bahwa 1) orang-orang di wilayah pegunungan Kota Ambon, Pulau Ambon mengenal dolmen dengan sebutan batu teong, yaitu batu yang melambangkan tentang pengelompokkan masyarakat yang terintegrasi. 2) Pola permukiman orang-orang di wilayah pegunungan Kota Ambon, Pulau Ambon berdasarkan budaya bendawi dolmen batu teong memiliki ciri permukiman mikro, yaitu permukiman yang menitik beratkan pusat dolmen batu teong sebagai sentral permukiman. Permukiman makro yaitu orang-orang di wilayah pegunungan Kota Ambon, Pulau Ambon memiliki ciri orientasi (kosmos) permukiman pantai–gunung. Orientasi tersebut dapat dilihat pada bentuk-bentuk permukiman yang linear memanjang mengikuti arah utara selatan serta kosmos mereka tentang membelah pulau, atau kata lain permukiman tidak mengikuti geografis panjang pulau.